Toward a Psychospiritual Pedagogy: Reconfiguring Emotional Intelligence in Inclusive Digital Education - Ayunda Nur Hanifah (Journal of Indonesian Digital Pedagogy, 2026)
This study aims to analyze the role of psychospiritual learning interventions in improving the emotional intelligence of children with special needs at Pusat Kegiatan Belajar Masyarakat (PKBM) Lentera Fajar Sidoarjo. The study uses a qualitative, ethnographic approach to explore the dynamics of children’s emotional intelligence development within the inclusive learning process. The analysis is based on Daniel Goleman’s five dimensions of emotional intelligence, namely self-awareness, self-management, motivation, empathy, and social skills. The results show that psychospiritual learning practices contribute to children’s emotional regulation, self-awareness, and social interaction with their surroundings. Learning practices such as mindfulness, positive affirmations, and self-reflection have been proven effective in helping children understand and manage their emotions more adaptively. In its implementation, the use of simple digital learning media—such as relaxation audio guides, multimedia-based reflection materials, and online learning resources—also supports the social-emotional learning process for children with special needs. Despite various challenges, such as differences in student responses and limited resources, educators’ and parents’ support is an important factor in the success of this intervention. The findings of this study indicate that the psychospiritual learning approach has the potential to serve as an alternative pedagogical strategy for strengthening emotional intelligence in inclusive education, one that is adaptive to the development of the digital learning environment.